An enhanced mixture method for constructing gatekeeping procedures in clinical trials. Issue 1 (2nd January 2018) - Kordzakhia, George; Brechenmacher, Thomas; Ishida, Eiji; Dmitrienko, Alex; Zheng, Winston Wenxiang; Li, David Fuyuan
ABSTRACT: It is increasingly common to encounter complex multiplicity problems with several multiplicity components in confirmatory Phase III clinical trials. These components are often based on several endpoints (primary and secondary endpoints) and several dose-control comparisons. When constructing a multiplicity adjustment in these settings, it is important to control the Type I error rate over all multiplicity components. An important class of multiple testing procedures, known as gatekeeping procedures, was derived using the mixture method that enables clinical trial sponsors to set up efficient multiplicity adjustments that account for clinically relevant logical relationships among the hypotheses of interest. An enhanced version of this mixture method is introduced in this paper to construct more powerful gatekeeping procedures for a specific type of logical relationships that rely on transitive serial restrictions. Restrictions of this kind are very common in Phase III clinical trials and the proposed method is applicable to a broad class of multiplicity problems. Several examples are provided to illustrate the new method and results of simulation trials are presented to compare the performance of gatekeeping procedures derived using this method and other available methods.